Análise da qualidade do serviço por meio da filosofia Lean Thinking: um estudo de caso na Comissão Geral de Licitação do município de Itacoatiara - Vasconcelos, Thaynara Reis (Brasil, 2024)
This research adopted a qualitative approach, focusing on the interpretation and meaning of the data collected in the natural environment. It used a case study at the Itacoatiara Municipality General Bidding Commission (CGLMI) to identify problems and propose improvements. It used techniques such as a bibliographic survey, questionnaires, Value Stream Mapping (VSM) and the 5S Program to analyze and improve processes, seeking to optimize the quality and efficiency of the services provided by the CGLMI. The results revealed that the bidding process had several points of inefficiency and waste, which had a direct impact on the quality and effectiveness of the services. The application of Lean Thinking principles, including the MFV and the 5S Program, made it possible to identify problem areas and propose significant improvements. As a result, there was a notable reduction in cycle time, elimination of unnecessary tasks and an overall improvement in service quality. In addition, the qualitative approach used in the research highlighted the importance of considering the subjectivity and interpretation of employees, which contributed to a more complete understanding of the challenges faced by the organization. These results indicate that applying Lean Thinking can be an effective strategy for improving service quality at Itacoatiara's General Bidding Commission and in similar organizations.